Assisting annotators of wearable activity recognition datasets through automated sensor-based suggestions - Günthermann, Lukas; Simpson, Ivor; Birch, Phil; Roggen, Daniel (Frontiers in Computer Science, 2025)
Wearable Activity Recognition consists of recognizing actions of people from on-body sensor data using machine learning. Developing suitable machine learning models typically requires substantial amounts of annotated training data. Manually annotating large datasets is tedious and time intensive. Interactive machine learning systems can be used to support this, with the aim of reducing annotation time or improving accuracy. We contribute a new web-based annotation tool for time series signals synchronized with a video recording with integrated automated suggestions, facilitated by ML models, to assist and improve the annotation process of annotators. This is enabled by focusing user attention toward points of interest. This is particularly relevant for the annotation of long periodic activities to allow fast navigation in large datasets without skipping start and end points of activities. To evaluate the efficacy of this system, we conducted a user study with 32 participants who were tasked with annotating modes of locomotion in a dataset composed of multiple long (over 12 h) consecutive sensor recordings captured by body-worn accelerometers. We analyzed the quantitative impact on annotation performance and the qualitative impact on the user experience. The results show that the implemented annotation assistance improved the annotation quality by 11% F1 Score but reduced annotation speed by 20%, whereas the NASA Task Load Index results show that participants perceived the assistance as beneficial for annotation speed but not for annotation quality.